1968
DOI: 10.1039/j19680000653
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and other studies of ruthenium dioxide and its hydrate

Abstract: The magnetic behaviour of ruthenium dioxide up to 1000°K is interpreted in terms of J being ca. -3000 cm.-l in dioxo-bridged chains of ruthenium atoms. The high electrical conductivity as well as certain structural features imply that the average oxidation state of the ruthenium atoms is substantially greater than +4.The oxide hydrate has a high surface area ; it is formulated as Ru02+,, yH,O since there can be an excess (chemisorbed) of oxygen particularly after removal of some of the water. Values of x up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 0 publications
5
37
0
Order By: Relevance
“…2(d). The value of 1.7 × 10 −4 emu/mol (300 K) is in good agreement with previous reports [8,17,18]. The 30% rise of the magnetic susceptibility with increased temperature from 300 K to 1000 K is also in excellent agreement with Fletcher et al [18], the only study that measured up to 1000 K. Our measurements, however, either produce a clear, broad maximum in the susceptibility or a significant leveling at the highest temperature, consistent with the presence of short-range ordering.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…2(d). The value of 1.7 × 10 −4 emu/mol (300 K) is in good agreement with previous reports [8,17,18]. The 30% rise of the magnetic susceptibility with increased temperature from 300 K to 1000 K is also in excellent agreement with Fletcher et al [18], the only study that measured up to 1000 K. Our measurements, however, either produce a clear, broad maximum in the susceptibility or a significant leveling at the highest temperature, consistent with the presence of short-range ordering.…”
supporting
confidence: 81%
“…The value of 1.7 × 10 −4 emu/mol (300 K) is in good agreement with previous reports [8,17,18]. The 30% rise of the magnetic susceptibility with increased temperature from 300 K to 1000 K is also in excellent agreement with Fletcher et al [18], the only study that measured up to 1000 K. Our measurements, however, either produce a clear, broad maximum in the susceptibility or a significant leveling at the highest temperature, consistent with the presence of short-range ordering. Due to the extreme difficulty in measuring small magnetic signals at such high temperature, which is near the limit of our instrument capability, as well as the possible loss of oxygen, different crystals produce slightly different behavior above 850 K. It is possible that this changing magnetic behavior above 900 K is related to the vanishing of the (100) peak and its underlying magnetic and/or structural order.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…As shown in Fig 3a, the Curie-Weiss parameter decreases as the samples are heated at higher temperatures, supporting previous indications that that electron delocalization or metallicity increases with decreasing water in the structure [3]. The TIP confirms that portions of the materials are metallic, or have delocalized electrons.…”
Section: Resultssupporting
confidence: 85%
“…A main absorption maximum at 310 nm for RuO 4 (oxidation state d 0 ) 17 has been published by Wells et al, 18 while the reflectance spectrum for RuO 2 (oxidation state d 4 ) 17 is reported to exhibit a broad band from 430 to 700 nm, centered at 585 nm. 19 Accounting for the width of the peak and the resolution of the spectrometer, our result clearly proves the presence of RuO 4 on the walls of the test-tube and thus the loss of ruthenium from the film during annealing in dry oxygen at 600ЊC.…”
Section: Resultsmentioning
confidence: 59%